Clinical Reproductive Medicine and Surgery A Practical Guide - Falcone, Tommaso; Hurd, William W.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Clinical Reproductive Medicine and Surgery offers a succinct overview of both the medical and surgical management of reproductive disorders, as well as coverage of associated imaging modalities. The book includes chapters on major reproductive endocrinology and infertility issues such as polycystic ovary syndrome and amenorrhea, management of endometriosis and fibroids (including interventional radiology), imaging modalities such as ultrasonography and sonohysterography, preservation of fertility, and recurrent pregnancy loss. Residents, fellows, and practitioners interested in reproductive endocrinology and infertility will find this focused and practical text invaluable.
Ovarian Hormones: Structure, Biosynthesis, Function, Mechanism of Action, and Laboratory Diagnosis -- Hypothalamic-Pituitary-Ovarian Axis and Control of the Menstrual Cycle -- Female and Male Gametogenesis -- Normal Puberty and Pubertal Disorders -- Fertilization and Implantation -- Reproductive Imaging -- Amenorrhea -- Polycystic Ovary Syndrome -- Abnormal Uterine Bleeding -- Menopause -- Male Infertility -- Female Infertility and Fertility Preservation -- Recurrent Early Pregnancy Loss -- Induction of Ovulation -- ART: Clinical and Laboratory Aspects -- Hysteroscopic Management of Intrauterine Disorders: Polypectomy, Myomectomy, Endometrial Ablation, Adhesiolysis, and Removal of Uterine Septum -- Gynecologic Laparoscopy -- Uterine Leiomyomas -- Tubal Disease and Ectopic Pregnancy -- Endometriosis -- Surgical Techniques for Management of Anomalies of the Müllerian Ducts.
Keywords: Medicine; Gynecology; Reproductive Medicine; Urology; Medicine & Public Health; Reproductive Medicine; Gynecology; Urology/Andrology.